Statius Silvae 1.3: A Stream and Two Villas. - Putnam, Michael C. J. (Illinois Classical Studies)
This essay presents a detailed literary analysis of Statius's Silvae 1.3 which honors Manilius Vopiscus and his Tiburtine villa. My reading follows the progress of the poem, as it first outlines the quality of the domain as a whole, then examines aspects of what a visitor might encounter. I survey Statius's varied use of ekphrasis and trace his patterns of allusion, especially to the work of Virgil. Eroticism is a salient theme throughout as is the importance of a series of bodies of water, especially the river Anio, to the poem's evolution.